Processing of carbon reinforced thermoplastic composites - Novo, P. J. (2020)
The aim of this work is to produce and optimize the processing of carbon fibres thermoplastic matrix pre-impregnated materials (towpregs and PCT´s) using the dry powder coating equipment from our own laboratories. Pultrusion was the selected manufacturing method for processing all carbon fibres thermoplastic matrix pre-impregnated materials into composite parts. The optimization of the pultrusion processe was made by studying the influence of the most relevant processing parameters in the final properties of the produced carbon fibres thermoplastic matrix pre-impregnated materials and composites. The composite relevant mechanical properties were determined and studied. The final composites were also submitted to Scanning Electron Microscopy (SEM), optical microscopy and calcination tests. The determination of the fiber volume fraction of a composite with a high melting temperature thermoplastic polymer used as matrix was obtained comparing the results of thermogravimetric analysis (TGA) with the calcination tests.